Preparation method of silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam drive well
By using a combination of alkaline silica sol and ammonium bentonite, the problem of poor blocking and blocking effect under high temperature conditions is solved, efficient steam throughput and steam well driving effect is achieved, and the blocking effect is improved. The high temperature resistance of the agent.
Patent Information
- Application Number
- CN202311004813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The prior art is difficult to effectively adjust and seal the flow channels in steam throughput and steam drive wells under high temperature conditions, especially in screen wells, and the high temperature resistance of the plug-in agent is insufficient.
Using alkaline silica sol and ammonium bentonite as the main components, the sealing agent is formed by combining alkaline silica sol and ammonium bentonite, and the gel curing effect of ammonium bentonite is used to form a stable silica gel to achieve Effective sealing of the strata.
It realizes a stable plug-in adjustment effect under high temperature conditions, avoids heat energy waste, improves steam throughput efficiency, and is also effective in the high permeability layer due to the stability of silica sol and the modification effect of ammonium bentonite. Work without failure.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oil production chemicals, and particularly relates to a method for preparing a silica sol-ammonium bentonite plugging and channeling blocking agent for steam throughput and steam drive wells. Background Art
[0002] At present, the domestic heavy oil is mainly produced by steam huff and puff. Since most heavy oil blocks have entered the middle and late development stage of high-cycle, low-pressure production, oil wells are affected by reservoir heterogeneity factors, and the phenomenon of steam channeling between wells is becoming increasingly serious. The high permeability layer repeatedly absorbs steam, while the medium permeability layer cannot be effectively used, resulting in waste of heat energy and a gradual deterioration of the huff and puff effect. Profile adjustment measures are needed. However, since some of these oil wells use mechanical screen completion technology, the plugging and channeling agent used in screen completion oil wells must be a non-granular solution or low-viscosity sol and have appropriate high temperature resistance.
[0003] At present, there are two commonly used and effective plugging and sealing agents: one is a solid-phase particle plugging and sealing agent mainly composed of rubber powder, fly ash, bark powder, etc. This series of profile control agents cannot enter the formation through the mechanical screen due to their particle state, so they cannot be used in screen completion oil wells; the other is organic polymer HPMA gel. Although it has good injectability, this gel has poor temperature resistance and will quickly decompose and disappear under conditions exceeding 150°C. Therefore, it cannot meet the domestic heavy oil steam huff and puff production method and steam drive wells. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a silica sol-ammonium bentonite plugging and sealing agent for steam throughput and steam drive wells with good high temperature resistance and a preparation method thereof.
[0005] The technical solution of the present invention is:
[0006] A silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam drive wells, which has the following special features:
[0007] The silica sol-ammonium bentonite plugging and sealing agent uses alkaline silica sol as a main agent and ammonium bentonite as a gel curing agent, wherein the composition according to mass percentage is as follows:
[0008] Alkaline silica sol 8% to 10%;
[0009] Ammonium bentonite 0.5% to 1.0%;
[0010] Water balance.
[0011] Furthermore, the alkaline silica sol has SiO2≥35%, pH value=9-10, and Na2O≤0.3%.
[0012] The ammonium bentonite used in the present invention is modified by dry extrusion ammoniumization. During the extrusion modification process, in addition to having a certain concentration of ammonium ions, a certain shear stress must be applied to crush the agglomerated bentonite particles, and even push the crystal layers layer by layer, thereby increasing the surface area of the natural calcium-based bentonite and accelerating the process of ammonium cations exchanging calcium ions. During the extrusion process, a part of the mechanical energy is converted into heat energy, which increases the temperature of the bentonite and promotes the NH4 + Cations and Ca 2+ The extrusion can also destroy the montmorillonite crystal structure, resulting in bond breakage. The exposed silicon ions, aluminum ions and oxygen ions are beneficial to the increase of bentonite adsorption capacity. The bond breakage also increases the negative charge on the surface of bentonite particles, making the ammonium modification more complete, and the optimal NH4 + Ion concentration is a necessary condition to ensure the smooth progress of the exchange reaction. The concentration of added ammonium ions must be greater than that of Ca 2+ The concentration is required to completely modify the natural calcium-based ammonium bentonite.
[0013] Furthermore, the preparation of the ammonium bentonite gel curing agent comprises the following steps:
[0014] (1) Modification of calcium-based bentonite raw materials
[0015] The natural calcium-based bentonite raw material is fed into the first roller extruder for roller extrusion, and a 4.5% ammonium salt aqueous solution is sprayed into the first roller extruder to crush and peel off the layered structure of the calcium-based bentonite, and NH4 + Ca2+ 2+ Then, the material extruded by the first roller extruder is sent to the second roller extruder for extrusion to make NH4 + With Ca 2+ Exchange modification reaction;
[0016] (2) Aging
[0017] The material after two times of extrusion by the roller mill was placed at room temperature for aging for 30 days;
[0018] (3) Drying
[0019] The aged material is dried in the sun until the water content is 25% ± 2%, and then dried at 250°C until the water content is 12% ± 1%. This drying temperature can ensure that the (NH4)2CO3 that has not been exchanged into the intercrystalline layers is fully decomposed to prevent these NH4 + The silica sol-ammonium bentonite plugging and sealing agent will gel before entering the formation or during the injection process;
[0020] (4) Crushing
[0021] The dried material was crushed into 325 meshes to obtain a powdered ammonium bentonite gel curing agent.
[0022] Furthermore, the ammonium salt is ammonium carbonate.
[0023] Furthermore, the amount of ammonium carbonate added is 3% to 8% of the mass of natural calcium-based bentonite.
[0024] On the other hand, a method for preparing a silica sol-ammonium bentonite plugging and sealing agent for steam throughput and steam drive wells is disclosed, and the specific steps are: stirring alkaline silica sol, ammonium bentonite and water at room temperature for 10 minutes, placing in a sealed tank, and obtaining a plugging and sealing agent for steam throughput and steam drive wells.
[0025] Furthermore, the stirring temperature is 25°C ± 5°C.
[0026] The construction process of the plugging and sealing agent for steam throughput and steam drive wells of the present invention can be selected as a general injection, and the silica sol-ammonium bentonite plugging and sealing agent is injected by using the injection and production pipe in the well; the construction is simple, the pipe does not need to be moved, and it is only necessary to control the construction injection pressure and displacement during construction. This injection method utilizes the heterogeneous permeability of the formation; when the working fluid is injected, the working fluid mainly enters the high permeability layer because the flow resistance of the high permeability layer is small; usually the high permeability layer is a high water-containing layer, and the plugging agent is needed to play a plugging role therein, so the different permeabilities of the formation can be used to achieve the purpose of selective injection of silica sol-ammonium bentonite plugging and sealing; general control and driving is mainly aimed at injection and production wells with complex well conditions, and the purpose of plugging is achieved by controlling the injection pressure and injection volume during construction; that is, the absorption capacity of the high permeability layer is reduced, and the absorption capacity of the low permeability layer is activated, thereby increasing the sweep coefficient.
[0027] With alkaline silica sol as the main agent, it is highly stable under room temperature conditions, will not undergo gel curing reaction by itself, and can be stored stably for a long time; the alkaline silica sol particles are spherical with a diameter between 1-100nm. In its microstructure, the interior of the particles is an irregular three-dimensional network structure composed of amorphous silicon dioxide, and the surface of the particles is covered with silanol (-Si-OH). The composition of silica sol is Na2O.nSiO2.mH2O, which will hydrolyze under the action of water to produce free sodium hydroxide. The further ionization of sodium hydroxide makes the silica sol solution show alkaline reaction. Similarly, the silica gel precipitated by hydrolysis in the silica sol can be peptized by its own sodium hydroxide, becoming a soluble silicate and ionized, generating a series of simple and complex ions, thereby forming a complex and free micelle. Therefore, silica sol is a complex system, and its solution is a colloidal solution that has both colloid characteristics and solution characteristics. In this system, the colloidal core in the center of the colloidal particle is an aggregate of silica dioxide, which has strong adsorption. Some SiO3 ionized in the glue 2- and OH -The anions are adsorbed by the nucleus, and some Na + Ions are adsorbed on SiO3 2- and OH - The anions are surrounded by colloid particles with a diameter of 1-100nm; the SiO3 adsorbed by the colloid core 2- and OH - ions and some of the closer Na + The ions form an adsorption layer, making the colloid particles negatively charged, and a portion of Na ions with opposite charges are loosely adsorbed around the colloid particles. + Ions, this part of Na + The ions form a diffusion layer;
[0028] Alkaline silica sol contains a large number of tiny discrete silicon dioxide solid particles. The surface area between the particles and the medium is very large, so the surface energy is very large, which is unstable from a thermodynamic point of view. However, from a kinetic point of view, whether the sol is stable or condensed under certain conditions depends on the two main forces between the particles, namely the van der Waals attraction between the particles and the electrostatic repulsion between the particles. Both are functions of potential energy. The relationship between the total potential energy of the combined action between particles and the distance shows that the total potential energy has an energy peak at a certain distance from the particle surface, that is, an energy barrier. The particles must cross this energy barrier to collide and aggregate. Under normal circumstances, the Brownian motion energy of the particles in the silica sol solution is not enough to cross the energy barrier, so the silica sol from a kinetic point of view is stable and may remain stable for a long time.
[0029] Ammonium bentonite is obtained by ion exchange reaction between natural calcium bentonite and ammonium agent, and is used as gel curing agent; the main component of bentonite, montmorillonite, is a layered aluminosilicate mineral, which is a 2:1 structure consisting of two Si-O tetrahedral sheets sandwiched by a layer of Al-O(OH) octahedral sheets. 4+ Partly Al 3+ Substitution, Al in octahedron 3+ Partly Mg 2+ , Fe 2+ , Zn 2+ Negative charges are generated by substitution, which need to be balanced by adsorbing exchangeable cations between the layers. Most of the Ca 2+ Ions form calcium bentonite. When the ammonium ionizer is mixed with calcium bentonite, the ammonium ions are exchanged into the crystal layer structure of montmorillonite to form ammonium bentonite;
[0030] The ammonium bentonite is NH4 + Ions replace the Ca in natural calcium-based bentonite 2+ The reaction mechanism is as follows:
[0031] Ca 2+- Bentonite + (NH4)2CO3 → 2NH4 + - Bentonite + CaCO3.
[0032] When alkaline silica sol neutralizes the adsorbed OH- or adds enough electrolytes, the zeta potential is reduced, the repulsion is reduced, the energy barrier is reduced, and the particles can easily cross the energy barrier and combine with each other, causing the sol to condense. When ammonium bentonite is mixed with silica sol solution and injected into the formation, the ammonium ions between the crystal layers are exchanged with the sodium ions in the silica sol solution and released from the crystal layers. Then the acid produced by the hydrolysis of ammonium ions neutralizes the sodium hydroxide in the silica sol, which will cause the silica sol gel to solidify and achieve the purpose of formation plugging.
[0033] The gelation and hardening mechanism of the silica sol-ammonium bentonite plugging and sealing agent in this application can be simply divided into two steps: the first step: the generation of silica gel; the second step: the dehydration and polymerization of silica gel. The formation process of silica gel determines the gelation and hardening process of silica sol. Silica sol solution is an alkali metal silicate, and the hydrolysis reaction of silica sol is as follows: Na2O.nSiO2+(2n+1)H2O→2Na2O+nSi(OH)4
[0034] Since the sodium oxide generated by the hydrolysis of silica sol has a peptizing effect on the silica gel, it will regenerate silicate. Therefore, the above hydrolysis reaction is in a reversible state, which is conducive to the stability of silica sol. At this time, the pH value of the silica sol aqueous solution is generally between 8.5-10.5. The stability of silica sol varies with the pH value of the solution. The larger the pH value, the smaller the polymerization rate of silica sol. When the pH is greater than 10.5, there is actually no polymerization, that is, the stability is the highest. On the contrary, as the pH value decreases, the polymerization of silica sol becomes greater and greater, until the pH value drops to 2-4-, the particles of silica sol change from negatively charged to positively charged. At this time, the silica sol solution is acidic and has good stability again. The reason why the silica sol solution is most stable at a pH value of 8.5-10.5 is that at this time, the surface charge density of the silica sol particles is large, the zeta potential is high, and the repulsive force between particles is dominant, so they will not collide with each other and gel, thus maintaining a stable state for a long time. When the pH value drops to 5-7, the charge on the particle surface decreases, the zeta potential decreases, and the particles are prone to collision and gelation. Therefore, when there is an acidic substance in the silica sol solution, the NaOH generated by the hydrolysis reaction can be neutralized, and the alkalinity of the solution can be reduced, thereby destroying the stability of the silica sol solution, intensifying the polymerization, and the silica gel will continue to precipitate and polymerize from the solution.
[0035] NH4 in ammonium bentonite crystal layer + In the silica sol solution, Na ionized with silica sol + The ions undergo an exchange reaction and enter the solution from the bentonite crystal layer, and the exchanged NH4 +Carry out hydrolysis reaction, and its ion reaction formula is: MMT-NH4 + +Na + →MMT-Na + +NH4 +
[0036] NH4 + +H2O→NH3+H3O +
[0037] That is, when the silica sol solution is mixed with ammonium bentonite, acids will gradually be generated. These acids will react with the alkali in the silica sol solution to neutralize it. The ion reaction formula is:
[0038] OH - +H3O + →2H2O
[0039] Therefore, as the reaction continues, the alkalinity in the mixed solution continues to decrease, and the equilibrium continues to shift to the right. Therefore, the role of the ammonium bentonite in this application is:
[0040] (1) reducing the Na2O content in the mixed solution to prevent the precipitated silica gel from being re-solubilized by alkali;
[0041] (2) Destroy the stable conditions of the silica sol solution, so that as the alkalinity in the mixed solution decreases, the silica gel will continue to precipitate and condense from the solution. As a result, the silica sol and ammonium ions will continue to hydrolyze, and the reaction will continue. The overall chemical reaction can be simply expressed as:
[0042] Na2O.nSiO2+2MMT-NH4 + +(n+1)H2O→2MMT-Na + +nSi(OH)4+2NH3
[0043] As the reaction time increases, the amount of gel increases, the colloidal layer around the particles thickens, and the original suspension gradually turns into a jelly-like substance containing a large amount of water, and then gradually hardens into a hard whole.
[0044] After adding ammonium bentonite to the silica sol solution, when the alkalinity gradually decreases to the condition that easily causes the silica gel to start polymerizing, the individual particles of the silica gel gradually polymerize and gel, and as the polymerization process continues, a polymer of silica gel is formed. The unstable -Si-OH group in the gel gradually forms a stable -Si-O-Si-body mesh gel structure, which can exist for a long time and block the formation channel. After that, under the long-term effect of the formation temperature, the silica gel continues to dehydrate and shrink, gradually turning into a rigid structure. In fact, this process is quite slow, especially the final dehydration and hardening process is slower.
[0045] The present invention introduces ammonium bentonite as a gel curing agent of alkaline silica sol into silica sol for the first time, develops a new oilfield plugging and channel sealing chemical, and solves the problem of plugging and channel sealing in high-temperature wells, especially screen wells. DETAILED DESCRIPTION
[0046] The performance of the silica sol-ammonium bentonite plugging and sealing agent of the present invention is further described below in conjunction with the examples.
[0047] The ammonium bentonite used in Example 1 of the present invention is prepared using Liaoning Jianping calcium bentonite and industrial ammonium carbonate produced by Taixing Experimental Chemical Plant as raw materials;
[0048] The silica sol-ammonium bentonite plugging and sealing agent of Example 2-Example 4 is prepared using the ammonium bentonite prepared in Example 1 and the commercial alkaline silica sol of Jinan Shouyue Chemical Technology Co., Ltd. as raw materials, wherein the alkaline silica sol indicators are SiO2≥35%, pH value = 9-10, and Na2O≤0.3%.
[0049] In Examples 2 to 4, the gel time is determined by the loss of fluidity of the silica sol-ammonium bentonite plugging and sealing agent in the sealed can; the gel strength is measured using a TA.GEL gel strength tester produced by Shanghai Baosheng Industrial Development Co., Ltd.
[0050] Example 1
[0051] (1) Modification of calcium-based bentonite raw materials
[0052] The natural calcium-based bentonite raw material from Jianping Shahai is fed into the first roller extruder for roller extrusion, and a 4.5% ammonium salt aqueous solution is sprayed into the extruder at the same time. The first roller extruder crushes and peels off the layered structure of the calcium-based bentonite, and NH4 + Ca2+ 2+ Then, the material extruded by the first roller extruder is sent to the second roller extruder for extrusion to make NH4 + With Ca 2+ Exchange modification reaction;
[0053] (2) Aging
[0054] The material after two times of extrusion by the roller mill was placed at room temperature for aging for 30 days;
[0055] (3) Drying
[0056] The aged material is dried in the sun until the water content is 25%, and then dried at 250℃ until the water content is 12%. This drying temperature can ensure that the (NH4)2CO3 that has not been exchanged into the intercrystalline layers is fully decomposed to prevent these NH4 + The silica sol-ammonium bentonite plugging and sealing agent working fluid will gel before entering the formation or during the injection process;
[0057] (4) Crushing
[0058] The dried material was crushed into 325 meshes to obtain a powdered ammonium bentonite gel curing agent.
[0059] Example 2
[0060] The materials were weighed in a ratio of 8% alkaline silica sol, 0.5% ammonium bentonite prepared in Example 1 and 91.5% tap water, stirred at room temperature (25° C.) for 10 minutes, and placed in a sealed tank to obtain a plugging and sealing agent for steam throughput and steam drive wells.
[0061] Gel strength test of plugging and channeling sealing agent for steam stimulation and steam drive wells:
[0062] The plugging and sealing agents for steam stimulation and steam drive were heated at 40℃, 80℃, 120℃ and 200℃ respectively. The gelling time was 162h, 54h, 24h and 9h respectively. The gelling strength was 1.31kg / cm 2 , 1.54kg kg / cm 2 , 2.40kgkg / cm 2 , 2.87kg kg / cm 2 .
[0063] Example 3
[0064] The materials were weighed in a ratio of 10% alkaline silica sol, 0.5% ammonium bentonite prepared in Example 1 and 89.5% tap water, stirred at room temperature (25° C.) for 10 minutes, and placed in a sealed tank to obtain a plugging and sealing agent for steam stimulation and steam drive wells.
[0065] Gel strength test of plugging and channeling sealing agent for steam stimulation and steam drive wells:
[0066] The plugging and sealing agents for steam stimulation and steam flooding were heated at 40℃, 80℃, 120℃ and 200℃ respectively. The gelling time was 120h, 35h, 15h and 5h respectively. The gelling strength was 1.851kg kg / cm 2 , 2.63kg kg / cm 2 , 3.41kg kg / cm 2 、3.87kg kg / cm 2 .
[0067] Example 4
[0068] Weigh the materials in the following proportions: 10% alkaline silica sol, 1.0% ammonium bentonite prepared in Example 1 and 89% tap water, stir at room temperature (25°C) for 10 minutes, and place in a sealed tank to obtain a plugging and channeling sealing agent for steam stimulation and steam flooding. Gel strength test of plugging and channeling sealing agent for steam stimulation and steam flooding:
[0069] The plugging and sealing agents for steam stimulation and steam flooding were heated at 40℃, 80℃, 120℃ and 200℃ respectively. The gelling time was 85h, 27h, 12h and 3h respectively. The gelling strength was 2.51kg kg / cm 2 , 3.37kg kg / cm 2 、3.95kgkg / cm 2 , 4.37kg kg / cm 2 .
[0070] The construction process of the plugging and channeling sealing agent for steam throughput and steam drive wells of the present invention can be selected by general injection, and the silica sol-ammonium bentonite plugging and channeling sealing agent is injected by using the injection and production pipe string in the well, and its advantages and effects are as follows:
[0071] 1. Safety of the construction process
[0072] The chemical properties of silica sol-ammonium bentonite plugging and sealing agent are very stable at room temperature. The release of ammonium ions of ammonium bentonite is often slow due to the restriction of the exchange reaction rate with sodium ions, so no gel reaction will occur during the injection process, and no "flash coagulation" out of control phenomenon will occur. There is enough stabilization time during the injection process and after entering the formation to ensure sufficient injection volume, as well as sufficient cleaning and recovery time for construction tools after injection.
[0073] 2. Good implantability
[0074] Silica sol-ammonium bentonite plugging and sealing agent is an aqueous solution, and its main agent silica sol is generally 1-100nm in particle size, while ammonium bentonite is converted from natural nano material bentonite, retaining layered structure and easy stripping, which ensures that silica sol-ammonium bentonite plugging and sealing agent can smoothly pass through the screen pipe into the formation, and there will be no situation where granular plugging agent cannot pass through the screen pipe due to bridging accumulation. In addition, the viscosity of silica sol-ammonium bentonite plugging and sealing agent slurry is low. Under room temperature (20℃), the initial viscosity of silica sol-ammonium bentonite plugging and sealing agent slurry is lower than <3mPa.s. The viscosity of silica sol-ammonium bentonite plugging and sealing agent with low content is equivalent to pure water, and after preparation, it can be maintained at least 5 days without obvious changes under ground conditions of normal temperature and pressure. The good injection performance of silica sol-ammonium bentonite plugging and sealing agent slurry can be injected using conventional injection equipment such as conventional profile control pumps and cement trucks.
[0075] 3. Adjustability of thickening and gel curing time
[0076] Silica sol-ammonium bentonite plugging and sealing agent will not gel and solidify by itself under the ground conditions of normal temperature and pressure. Special gel curing agent and certain temperature are two basic conditions to start its gel curing reaction. Therefore, the gelation and curing speed of silica sol-ammonium bentonite plugging and sealing agent slurry in the formation can be controlled by temperature and gel curing agent, and its gel time can be adjusted within the range of several hours. Therefore, silica sol-ammonium bentonite plugging and sealing agent can fully meet the profile control and sealing operations of various scales.
[0077] 4. Restoration of formation produced fluid channel
[0078] The elastic gel of the silica sol-ammonium bentonite plugging and sealing agent will slowly release the water contained in it under the influence of the formation temperature, and the volume will gradually shrink, eventually forming a hard and transparent glass-like adhesive to firmly bond the formation sand together. The gradual shrinkage of the gel means that the formation production channel has been restored, which just meets the requirements of the steam huff and puff technology for plugging agents. At the same time, the shrinkage process of the gel volume also means that its plugging and sealing function is basically over, and the bottom permeability gradually recovers. Therefore, the plugging and sealing agent has little damage to the oil layer.
[0079] 5. Good temperature resistance
[0080] After the silica sol-ammonium bentonite plugging and sealing agent undergoes gel reaction, it first generates an elastic inorganic jelly structure, in which the particles of the structure are combined in the form of chemical bonds, and the inorganic sol and a large amount of water are filled in it. Under the action of the gel curing agent and the formation temperature, the sol particles in this jelly structure will gradually undergo cross-linking reactions to form new -Si-O-Si- chemical bonds, causing the chemical bond density in the jelly to gradually increase, the average distance between the particles to gradually shorten, and the water in the jelly to be gradually driven out, the volume of the jelly to gradually decrease, and the hardness to gradually increase. As the heating time passes, it enters the gel stage until it enters the final vitreous stage, completing the entire change process; however, no matter which stage of the silica sol-ammonium bentonite plugging and sealing agent is in the above-mentioned jelly, gel and vitreous body, the HPAM jelly will not be easily degraded by temperature, even at the high temperature of steam injection, and the high temperature will never cause it to decompose and disappear. Therefore, this material has good high temperature resistance and is very suitable for plugging and sealing of steam wells.
[0081] 6. Removability
[0082] The gel initially formed by silica sol-ammonium bentonite plugging and sand blocking agent can be dissolved in a strong alkaline solution. Therefore, if an error is found after construction, a strong alkaline solution can be injected to immediately release the generated gel plugging. This material is composed of a mixture of alkaline silica sol and nano ammonium bentonite. During construction, it can smoothly pass through the mechanical screen to enter the high permeability channel. At the formation temperature, it first solidifies into an inorganic elastic gel overall plugging material. The inorganic elastic gel will slowly shrink under the continuous action of the formation temperature, and the shrinkage rate can reach more than 80-90%, and finally form a hard and transparent glass-like film layer, and firmly bond the formation sand together. Therefore, this material initially blocks the cross-flow channel with a large volume of gel, which plays a role in adjusting the profile; as time goes by, the gel volume gradually shrinks, the plugging effect gradually decreases, and the blocked formation fluid production channel is gradually released; finally, it solidifies into a hard glass-like thin layer to firmly bond the formation sand together, minimizing the pollution to the formation and avoiding permanent damage to the formation.
[0083] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silica sol-ammonium bentonite plugging and channeling sealing agent for steam throughput and steam flooding, characterized by: The silica sol-ammonium bentonite plugging and sealing agent uses alkaline silica sol as a main agent and ammonium bentonite as a gel curing agent, wherein the composition according to mass percentage is as follows: Alkaline silica sol 8% to 10%; Ammonium bentonite 0.5%~1.0%; Water balance; The alkaline silica sol has SiO2≥35%, pH value=9-10, and Na2O≤0.3%.
2. The silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam flooding according to claim 1 is characterized by: The preparation of the ammonium bentonite gel curing agent comprises the following steps: (1) Modification of calcium-based bentonite raw materials The natural calcium-based bentonite raw material is fed into the first roller extruder for roller extrusion, and a 4.5% ammonium salt aqueous solution is sprayed into the first roller extruder to crush and peel off the layered structure of the calcium-based bentonite, and NH4 + Ca2+ 2+ Then, the material extruded by the first roller extruder is sent to the second roller extruder for extrusion to make NH4 + With Ca 2+ Exchange modification reaction; (2) Aging The material after two times of extrusion by the roller mill was placed at room temperature for aging for 30 days; (3) Drying The aged material is dried in the sun until the moisture content is 25% ± 2%, and then dried at 250°C until the moisture content is 12% ± 1%; (4) Crushing The dried material was crushed into 325 meshes to obtain a powdered ammonium bentonite gel curing agent.
3. The silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam flooding wells according to claim 2 is characterized by: The ammonium salt is ammonium carbonate.
4. The silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam flooding well according to claim 3 is characterized by: The amount of ammonium carbonate added is 3% to 8% of the mass of natural calcium-based bentonite.
5. The method for preparing the silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam flooding wells according to claim 1, characterized in that: The alkaline silica sol, ammonium bentonite and water were stirred at room temperature for 10 minutes and placed in a sealed tank to obtain a plugging and sealing agent for steam stimulation and steam flooding wells.
6. The method for preparing the silica sol-ammonium bentonite plugging and sealing agent for steam stimulation and steam flooding wells according to claim 5, characterized in that: The stirring temperature is 25℃±5℃.
Citation Information
Patent Citations
Heat-resisting interpenetrating polymer network plural gel profile control agent and preparation method thereof
CN106634908A
Preparation method of high-performance lithium-based bentonite
CN114853026A
